(untitled) (Academicia Globe: Inderscience Research, 2023)
Uzbekistan, with its rich cultural heritage and stunning landscapes, is increasingly becoming a popular destination for tourists around the world. However, as the tourism industry grows, it is crucial to prioritize sustainable practices and promote healthy ecotourism. Ecotourism, which focuses on responsible travel and environmental conservation, can play a vital role in preserving Uzbekistan’s natural wonders and cultural sites for future generations. This article explores the importance of developing healthy ecotourism in Uzbekistan and the potential benefits it can bring to the country.